2012
DOI: 10.1002/jcb.24009
|View full text |Cite
|
Sign up to set email alerts
|

The JMJD2A demethylase regulates apoptosis and proliferation in colon cancer cells

Abstract: JMJD2A is a transcriptional cofactor and enzyme that catalyzes demethylation of histone H3 lysines 9 and 36 and is overexpressed in human tumors, but its role in oncogenesis remains unclear. Here, we show that JMJD2A interacts with the tumor suppressor p53 both in vitro and in HCT116 colon cancer cells. Chromatin immunoprecipitation assays demonstrated that JMJD2A was recruited together with p53 to the promoter of the p21 cell cycle inhibitor upon stimulation with the DNA damaging agent, adriamycin. Downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 47 publications
5
91
1
Order By: Relevance
“…Flag-KDM4A-WT or Flag-KDM4A (K3R) expression vectors were co-transfected with HA-tagged p53 vector into 293 T cells and immunoprecipitation assays were performed. Consistent with a previous report (Kim et al 2012), Flag-KDM4A strongly interacted with HA-tagged p53. In contrast, mutation of sumoylation sites within KDM4A reduced the interaction between p53 and KDM4A (Figure 4(A)).…”
Section: Sumoylation Facilitates the Interaction Between Kdm4a And P53supporting
confidence: 92%
See 4 more Smart Citations
“…Flag-KDM4A-WT or Flag-KDM4A (K3R) expression vectors were co-transfected with HA-tagged p53 vector into 293 T cells and immunoprecipitation assays were performed. Consistent with a previous report (Kim et al 2012), Flag-KDM4A strongly interacted with HA-tagged p53. In contrast, mutation of sumoylation sites within KDM4A reduced the interaction between p53 and KDM4A (Figure 4(A)).…”
Section: Sumoylation Facilitates the Interaction Between Kdm4a And P53supporting
confidence: 92%
“…KDM4A-deficient cells exhibit upregulation of p53 target gene (p21, bcl2) expression and lead to reduced colon cancer cell proliferation (Kim et al 2012). Here, we demonstrated that KDM4A was modified by SUMO1, and that this sumoylation was involved in the binding between KDM4A and p53.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations